Unveiling the therapeutic potential of Lobaria extract and its depsides/depsidones in combatting Aβ42 peptides aggregation and neurotoxicity in Alzheimer’s disease - Yang, Meixia; Yan, Caishan; Ospondpant, Dusadee; Wang, Lisong; Lin, Shengying; Tang, Wai Lun; Dong, Tina Tingxia; Tong, Penger; Xu, Qin; Tsim, Karl Wah Keung (Frontiers in Pharmacology, 2024)
The development of effective inhibitors that can inhibit amyloid β (Aβ) peptides aggregation and promote neurite outgrowth is crucial for the possible treatment of Alzheimer's disease (AD). In this study, we conducted systematic approaches with biophysical and cellular methods to investigate the potential effect of water and ethanol extracts deriving from Lobaria, as well as its main depsidones and depsides (DEPs) on the aggregation and disaggregation of Aβ42, Aβ42-mediated cell toxicity, and neuronal differentiation in cultured PC12 cells. It was found that Lobaria extracts, and its DEPs inhibited effectively Aβ42 fibrillation and disaggregate mature Aβ42 fibrils. Notably, the ethanol extract of Lobaria demonstrated superior dual inhibitory effects, as compared to the water extract. Among the three DEPs tested, gyrophoric acid was found to be the most effective phytochemical. Additionally, the herbal extract-treated Aβ42 aggregation species significantly protected neuronal cells from Aβ42-induced damage and effectively promoted neurite outgrowth. Given that Lobaria is commonly used in ethnic medicine and food with good safety records, our results propose that Lobaria extracts, and its DEPs, could have great potential in developing as neuroprotective and therapeutic agents for AD patients.